Clinical Presentation of Spasticity and Passive Range of Motion Deviations in Dyskinetic Cerebral Palsy in Relation to Dystonia, Choreoathetosis, and Functional Classification Systems. (3rd April 2021) - Bekteshi, Saranda; Vanmechelen, Inti; Konings, Marco; Ortibus, Els; Feys, Hilde; Monbaliu, Elegast
ABSTRACT: Objectives : To map the presence, severity, and distribution of spasticity and passive range of motion (pROM) deviations in dyskinetic cerebral palsy (DCP), and to explore their relation with dystonia, choreoathetosis, and functional abilities. Methods : This cross-sectional study included 53 participants with DCP. Spasticity was assessed with the Modified Ashworth Scale, limited- and increased pROM (hypermobility) with a goniometer, dystonia and choreoathetosis with the Dyskinesia Impairment Scale, gross motor and manual abilities with corresponding functional classification systems. Results : Spasticity and limited pROM were correlated with dystonia of the upper limbs (0.41< rs <0.47, <0.001 <  p < .002) and lower limbs (0.31< rs <0.41, 0.002 <  p < .025), and both functional systems of gross motor (0.32< rs <0.51, <0.001 <  p < .018) and fine manual abilities (0.34< rs <0.44, 0.001 <  p < .014). Hypermobility is correlated only with choreoathetosis of the lower limbs (0.44, p = .001). Conclusions : Coexisting spasticity and pROM deviations in DCP are functionally limiting and should be addressed accordingly. Hypermobility may lead to an increased luxation risk.